The Impact of COVID-19 on Medical Examinations - Harky, Amer; Karimaghaei, Donia; Katmeh, Hannah; Hewage, Savini (Acta Biomedica Atenei Parmensis, 2020)
Background and aim The coronavirus-19 (COVID-19) pandemic has had a profound impact on many aspects of our lives, including medical education. The suspension of clinical placements and cancellation of objective structured clinical examinations (OSCE) is likely to have an influence on students’ performance. Methods Using a questionnaire, a retrospective observational study was conducted. Our primary focus was 3rd year medical students following their examinations in May 2020. Results Out of 46 responses obtained, the results demonstrated over 2/3 felt they perform better in clinical OSCE compared to written examinations and the majority performed worse this year during the pandemic. On a Likert scale, a mean result of 3/5 was obtained for confidence upon returning to placement and to address this, most stated they would benefit from extra optional teaching. Additionally, a further average of 3.82 was derived to represent how greatly students believed the absence of third year clinical OSCE would negatively impact their performance in the OSCE for the following academic year. Conclusion The results of our study highlight that the cancellation of clinical placements and OSCE due to coronavirus has negatively impacted on medical education and if we are to be faced with future pandemics, we must be better prepared to train future doctors.